1986
DOI: 10.1080/07315724.1986.10720112
|View full text |Cite
|
Sign up to set email alerts
|

Serum alkaline phosphatase in diabetes mellitus.

Abstract: Elevation of serum alkaline phosphatase concentration in patients with diabetes mellitus has been observed for several years, but the source and reasons are unknown. We report our experience with 39 diabetics, 38% of whom had an unexplained elevation of serum alkaline phosphatase. Isoenzyme determinations revealed bone fraction as the predominant species. Mean fasting serum glucose was significantly higher in the group with elevated alkaline phosphatase, supporting an association between the severity of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
1
18
3
Order By: Relevance
“…Osteocalcin is also a marker of bone turnover, when bone formation and resorption are coupled [25]. An increase in serum alkaline-phosphatase, derived from bone, is frequently found in diabetic patients [26,27], but in the present study serum leucine amino peptidase also decreased after glycemic control. It is not concluded that the decrease in serum total alkaline-phosphatase was due to the change in its iso-enzyme from bone.…”
Section: Discussioncontrasting
confidence: 28%
“…Osteocalcin is also a marker of bone turnover, when bone formation and resorption are coupled [25]. An increase in serum alkaline-phosphatase, derived from bone, is frequently found in diabetic patients [26,27], but in the present study serum leucine amino peptidase also decreased after glycemic control. It is not concluded that the decrease in serum total alkaline-phosphatase was due to the change in its iso-enzyme from bone.…”
Section: Discussioncontrasting
confidence: 28%
“…[56] Both ALP and phosphate levels are more effective in predicting the risk of total mortality of people with diabetes and cardiovascular diseases. It is reported that 38% of diabetic patients have elevated serum alkaline phosphatase levels, mean fasting serum glucose level is positively associated with ALP, and bone ALP is the predominant type, which may be caused by diabetic bone diseases [57]. Indeed 9 out of 15 studies on the association of phosphate level with total mortality have shown an ascending incidence of diabetes in higher categories of phosphate (data now shown).…”
Section: Discussionmentioning
confidence: 90%
“…Heazell et al 2006 reported a case of pregnancy complicated by gestational diabetes and hypertension in which extremely high elevation of bone specific isoenzyme of alkaline phosphatase was noted during labour this lead to elevation in total serum alkaline phosphatase which couldn’t be assume to arise from placenta. [5354]…”
Section: Discussionmentioning
confidence: 99%